Investigating the influence of free volume and temperature on time-temperature superposition principle by MD simulation - Shihong YUAN; Takenobu SAKAI (Mechanical Engineering Journal)
Polymers and their composites are extensively utilized in the aerospace, energy, and automotive industries due to their lightweight properties, ease of manufacturing, high impact resistance, and other advantages. These materials are crucial for applications where performance and durability under varying environmental conditions are critical. Accurately predicting the viscoelastic behavior of polymers is essential for ensuring their reliability and durability. The time-temperature superposition principle (TTSP) is widely used to predict long-term viscoelastic properties, such as creep and stress relaxation, by making a master curve from short-term experimental data at various temperatures. Despite its widespread application, the molecular mechanisms of TTSP are not fully understood. To approach this issue, molecular dynamics (MD) simulations were employed to investigate TTSP mechanisms at the molecular level. Creep analyses were conducted at various temperatures with both with constant density and pressure using polypropylene as the model polymer to examine the effect of density on TTSP. The purpose of the simulations is to explain the basic mechanisms causing viscoelastic behavior, including the effect of chain interactions, potential energy changes, and free volume changes. The results indicate that the change of free volume has an important role in the formation of the TTSP master curve. Additionally, torsional potential energy is highly responsive to temperature changes, whereas non-bonding potential energy is more influenced by density changes. Furthermore, a linear relationship was found between changes in internal molecular angles (bond angle and torsion angle) and molecular chain structures (kinks and entanglements) with shear creep compliance.